THE MARKET IDEOLOGY BEHIND THE DEVELOPMENT OF KANDA PAT TEACHINGS IN BALI IN THE GLOBAL ERA - Aryadi Putra, Jro Made Gede; Adiputra, Nyoman; Suarka, I Nyoman; Anom Kumbara, A.A. Ngurah (E-Journal of Cultural Studies, 2021)
Tourism as an introduction to Balinese culture in the era of globalization with the development of the global tourism business. On the other hand, the emergence of a spiritual school of kebatinan which is proficient with Kanda Pat's style, grows, exists and develops in Bali. Local adaptation causes variation or diversity in responding to a culture. In globalization there is a local response or adaptation to the globalization uniformity project. This response made Kanda Pat's teachings globalized, as a genius local science that began to globalize. Based on these ideas, in this research there are several things to be examined related to the existence of Kanda Pat's teachings in the Balinese social environment. From the description of the background, it generally aims to reveal the phenomenon of the market ideology behind the development of Kanda Pat's teachings in Bali in the global era. In addition to general objectives it also has specific objectives, the specific objectives of this study are (1) knowing the shape of Kanda Pat in Balinese culture, (2) knowing the social and economic benefits of developing Kanda Pat's teachings as a healing tourism. Based on the discussion of this research, it is found that the existence of Kanda Pat is a great cultural wealth of Balinese people, which is commodified as tourism healing to have socio-economic, spiritual and health functions in line with tourism developments and postmodern lifestyle trends.  Keywords : market ideology, kanda pat teachings, tourism, healig. glucasization